2018
DOI: 10.1111/resp.13324
|View full text |Cite
|
Sign up to set email alerts
|

Individualized breathlessness interventions may improve outcomes in patients with advanced COPD

Abstract: This feasibility study of individualized breathlessness interventions in patients with severe COPD and refractory breathlessness is the first to demonstrate a clinically significant reduction in dyspnoea scores, with high levels of patient acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…If, for example, certain athletes are deemed to have a profile that is related to being susceptible to doping or they have a favorable attitude toward doping, they could be exposed to an individualized education program, which reflects their scores on other elements of the SDCM-AA. Evidence from other domains, such as education and medicine, revealed that individualized interventions are superior to generic interventions (e.g., Qian et al, 2018;Chen et al, 2019;Partanen et al, 2019). Published interventions designed to reduce doping prevalence have not differentiated between individuals and thus considered individual athletes' existing knowledge, attitudes, or susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…If, for example, certain athletes are deemed to have a profile that is related to being susceptible to doping or they have a favorable attitude toward doping, they could be exposed to an individualized education program, which reflects their scores on other elements of the SDCM-AA. Evidence from other domains, such as education and medicine, revealed that individualized interventions are superior to generic interventions (e.g., Qian et al, 2018;Chen et al, 2019;Partanen et al, 2019). Published interventions designed to reduce doping prevalence have not differentiated between individuals and thus considered individual athletes' existing knowledge, attitudes, or susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al . conducted a pilot study of a breathlessness intervention in advanced COPD . A combination of education, breathing techniques, a hand鈥恏eld fan and selective use of oxygen, opioids and anxiolytics led to significant improvements in quality of life .…”
Section: Copdmentioning
confidence: 99%
“…conducted a pilot study of a breathlessness intervention in advanced COPD . A combination of education, breathing techniques, a hand鈥恏eld fan and selective use of oxygen, opioids and anxiolytics led to significant improvements in quality of life . An editorial called for randomized controlled trials to assess which components of the intervention are most beneficial …”
Section: Copdmentioning
confidence: 99%
“…In a recent publication in Respirology , a small pilot trial provides hope for the field and more importantly to the patients suffering from this life impairing symptom . Qian et al .…”
mentioning
confidence: 99%
“…In a recent publication in Respirology, a small pilot trial provides hope for the field and more importantly to the patients suffering from this life impairing symptom. 2 Qian et al were able to complete a study in 26 of 32 COPD patients suffering from severe dyspnoea. Variables including dyspnoea, health status and anxiety and depression were evaluated at baseline and 6 weeks after a dyspnoea-directed multidimensional intervention.…”
mentioning
confidence: 99%